Therapeutic exercise for articular disc disorders and degenerative joint disease of TMJ: Approach and techniques of therapeutic exercise performed by a specialist - TAGUCHI, Nozomu (Journal of the Japanese Society for the Temporomandibular Joint, 2020)
Reversible conservative treatment, especially therapeutic exercise, has attracted attention as a first-line initial treatment for temporomandibular disorders. In the field of orthopedics, therapeutic exercise has been established as an important conservative treatment, but further examination regarding its use for the treatment of temporomandibular disorders is needed.Here, we explain the approach and techniques of therapeutic exercise (i.e., temporomandibular joint mobilization therapy) performed by a specialist according to the pathological condition of patients with articular disc disorder/degenerative joint disease (DJD). Furthermore, based on the degree of joint dysfunction classification, temporomandibular joint motion exercise (TMJROME) and self-traction therapy (STT) as self-care at the initial visit and at the first return visit were provided for patients with moderate or severe disability as a single exercise program, and when they were administered, the clinical symptoms (the five items of maximal mouth opening, pain at rest, pain upon opening and closing, pain upon mastication, and degree of difficulty in daily life) were evaluated.The results revealed a significant improvement for maximal mouth opening, pain upon opening and closing, pain upon mastication, and degree of difficulty in performing activities of daily living (p<0.05).It appears that these therapeutic exercises circulate the synovial fluid, expand the joint cavity, and ameliorate the range of motion of the joint. Thus, the results suggest that these therapeutic exercises may be effective conservative treatments that reduce symptoms associated with articular disc disorder, especially cases of anterior temporomandibular joint disc displacement without reduction (ADDwoR) and DJD, in a relatively short period of time.